DNA methylation from germline cells in veterans with PTSD. (September 2019) - Mehta, Divya; Pelzer, Elise S.; Bruenig, Dagmar; Lawford, Bruce; McLeay, Sarah; Morris, Charles P.; Gibson, John N.; Young, Ross McD.; Voisey, Joanne
Abstract: In this study we investigated genome-wide sperm DNA methylation patterns in trauma-exposed Vietnam veterans. At the genome-wide level, we identified 3 CpG sites associated with PTSD in sperm including two intergenic and one CpG within the CCDC88C gene. Of those associated with PTSD in sperm at a nominal level, 1868 CpGs were also associated with PTSD in peripheral blood (5.6% overlap) including the RORA, CRHR1 and DOCK2 genes that have been previously implicated in PTSD. A total of 10 CpG sites were significantly associated with a reported history of a diagnosed mental health condition in children and reached genome-wide significance. CpGs associated with a history of a reported mental health condition in children were also enriched (90% of tested genes) for genes previously reported to be resistant to demethylation, making them strong candidates for transgenerational inheritance. In conclusion, our findings identify a unique sperm-specific DNA methylation pattern that is associated with PTSD.